(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This comparative study explores the divergent marketing strategies employed by fast food outlets in urban and rural areas of India. By relying exclusively on secondary data from credible sources such as industry reports, academic journals, government publications and brand websites, the study reveals significant variations in promotional channels, customer engagement methods, pricing, menu adaptations and target audiences. Urban fast food outlets predominantly focus on digital advertising, app-based promotions and influencer collaborations aimed at younger, tech-savvy consumers. In contrast, rural outlets emphasize traditional media like radio and newspapers, offer value-driven pricing and engage in community-centric activities such as local sponsorships and events. Menu designs also reflect regional preferences, with urban markets favoring gourmet and global options while rural areas prefer hearty, familiar meals. The findings underscore the importance of contextual marketing tailored to demographic, economic and cultural distinctions. This study contributes to a nuanced understanding of consumer engagement and strategic brand positioning in diverse market settings across India.